PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR AKUNTANSI SISWA KELAS XI AKUNTANSI DI SMK NEGERI 1 GOWA - ,, Hajariah; Hasyim, Ahmad (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
The main objectives of this research are: Improving the learning outcomes of Class XI Accounting Students through the application of Problem Based Learning learning models at State 1 Gowa Vocational School. This type of research is Classroom Action Research (CAR). This research was carried out on 32 subjects of XI Accounting research at State 1 Gowa Vocational School. The results showed that: The application of the Problem Based Learning learning model could improve the accounting learning outcomes of the 11th grade students of Accounting at the State Vocational School 1 Gowa ". The main objectives of this research are: Improving the learning outcomes of Class XI Accounting Students through the application of Problem Based Learning learning models at State 1 Gowa Vocational School. This type of research is Classroom Action Research (CAR). This research was carried out on 32 subjects of XI Accounting research at State 1 Gowa Vocational School. The results showed that: "The application of Problem Based Learning learning models can improve accounting learning outcomes for eleventh grade students of Accounting at 1 Gowa State Vocational High School". Indications of improvement in learning outcomes can be seen from the increasing trend of student learning outcomes from the initial conditions, cycle I, and cycle II, and the achievement of completeness of student learning outcomes in cycles I and II, as follows: Implementation of cycle I actions, obtained student learning outcomes, average the value of 45, the standard deviation 15, then the students who complete there are 5 people or 15.63%, students who are not complete there are 27 people or 84.38%. In the implementation of the second cycle of action student learning outcomes increased, with a total value of 2,319, an average score of 72, a standard deviation of 7, then complete students there were 28 people or 87.50%, students who did not complete there were 4 people or 12.50%. Thus both individually and classically exceed the achievement indicators of the KKM, which is 70 for individual achievement scores and 70% for KKM class achievements. Keywords: Problem Based Learning Learning Model, Learning Outcomes